2015
DOI: 10.1016/j.scitotenv.2015.03.026
|View full text |Cite
|
Sign up to set email alerts
|

UV filters bioaccumulation in fish from Iberian river basins

Abstract: The occurrence of eight organic UV filters (UV-Fs) was assessed in fish from four Iberian river basins. This group of compounds is extensively used in cosmetic products and other industrial goods to avoid the damaging effects of UV radiation, and has been found to be ubiquitous contaminants in the aquatic ecosystem. In particular, fish are considered by the scientific community to be the most feasible organism for contamination monitoring in aquatic ecosystems. Despite that, studies on the bioaccumulation of U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(71 citation statements)
references
References 38 publications
3
67
1
Order By: Relevance
“…Similar concentrations were found in Taiwan for ES, HMS, BP3, BP1 and BP8 ranging 0.5 and 6.9 ng/g-dw for wild fish (Tsai et al, 2014). Higher levels were found in wild fish, in samples from Spain for EMC at 241.7 ng/g-dw (Gago-Ferrero et al, 2015; and from Norway for BP3 at 1037 ng/g-dw and OC at 11875 ng/g-dw (Langford et al, 2015). Besides the high concentrations of UV-filters in codfish, Langford et al (2015) also detected levels of BP3, EMC and OC in prawns Pandalus borearis (BP3 at 68.4, OC at 23.1 ng/g-dw).…”
Section: Occurrence In Biotasupporting
confidence: 72%
“…Similar concentrations were found in Taiwan for ES, HMS, BP3, BP1 and BP8 ranging 0.5 and 6.9 ng/g-dw for wild fish (Tsai et al, 2014). Higher levels were found in wild fish, in samples from Spain for EMC at 241.7 ng/g-dw (Gago-Ferrero et al, 2015; and from Norway for BP3 at 1037 ng/g-dw and OC at 11875 ng/g-dw (Langford et al, 2015). Besides the high concentrations of UV-filters in codfish, Langford et al (2015) also detected levels of BP3, EMC and OC in prawns Pandalus borearis (BP3 at 68.4, OC at 23.1 ng/g-dw).…”
Section: Occurrence In Biotasupporting
confidence: 72%
“…Nevertheless, 4-MBC is potentially dangerous for two reasons: 1) its estrogenic activity can directly be harmful to humans who abundantly use products where it is contained; 2) its dispersion in water and its consequent bioaccumulation in aquatic species poses a serious environmental concern. In fact, a high bioaccumulation of UV filters was demonstrated in seawater samples from beaches in Gran Canaria Island (Rodriguez Sanchez et al, 2015), and high levels of 4-MBT were found in fish from Iberian river basins (Gago-Ferrero et al, 2015). Another widely diffused UV filter is benzophenone 2 (BP-2).…”
Section: Synthetic Xenoestrogens: Endocrine Disrupting Chemicals (mentioning
confidence: 99%
“…Significant amounts of these emerging contaminants are being discharged into the environment via treated and untreated wastewater, recreational activities, and other human activities. As a result, they have been widely detected in rivers, lakes, seas, groundwater, and organism tissues [9,[14][15][16][17][18][19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…TCC) were found to be fairly persistent [7,24,32]. Accumulation of these emerging contaminants in sediment may pose risks to wildlife, especially benthic and sediment-dwelling organisms because these chemicals can be bio-accumulative in organisms and even be biotransferable in food chains [4,17,33,34].…”
Section: Introductionmentioning
confidence: 99%